Dynamics of the immune microenvironment and immune cell PANoptosis in colorectal cancer: recent advances and insights - Jinlong Wan; Jianzhong Zhao; Xiaolu Fang (Frontiers in Immunology)
Colorectal cancer (CRC) is one of the most significant oncological threats to human health globally. Patients often exhibit a high propensity for tumor recurrence and metastasis post-surgery, resulting in suboptimal prognoses. One of the underlying reasons for the metastatic potential of CRC is the sustained abnormal state of the tumor immune microenvironment, particularly characterized by the atypical death of critical immune cells. In recent years, a novel concept of cell death known as PANoptosis has emerged. This form of cell death is regulated by the PANoptosome complex and encompasses key features of apoptosis, pyroptosis, and necroptosis, yet cannot be entirely substituted by any of these processes alone. Due to its widespread occurrence and complex mechanisms, PANoptosis has been increasingly reported in various malignancies, enhancing our understanding of its pathological mechanisms, particularly in the context of CRC. However, the characteristics of immune cell PANoptosis within the CRC immune microenvironment have not been thoroughly elucidated. In this review, we focus on the impact of CRC progression on various immune cell types and summarize the distinctive features of immune cell PANoptosis. Furthermore, we highlight the future research trends and challenges associated with the mechanisms of immune cell PANoptosis in CRC.